2001
DOI: 10.1081/jdi-100104735
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria in Focal Segmental Glomerulosclerosis: Role of Circulating Factors and Therapeutic Approach

Abstract: The clinical course of primary Focal Segmental Glomerulosclerosis (FSGS) is frequently complicated by nephrotic range proteinuria and progression to renal failure. The high recurrence rate of the disease in transplanted kidney suggests the hypothesis that such patients have a circulating factor that alters glomerular capillary permeability. In recent years some authors found that serum from patients with FSGS increases glomerular permeability to albumin and partially identified the permeability factor (PF) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In all the patients with significant proteinuria, we started treatment with immunoadsorption or plasmapheresis as soon as possible because previous studies demonstrated that success of treatment was better with an early start (9). Immunoadsorption and plasmapheresis represent the most common therapeutic approach with complete or partial remission of proteinuria achieved in 65% of treated adults as shown by retrospective studies (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Prior to the routine use of plasmapheresis graft failure owing to recurrent FSGS was up to 80% (10).…”
Section: Plasmapheresis In Fsgs Recurrence 441mentioning
confidence: 99%
See 1 more Smart Citation
“…In all the patients with significant proteinuria, we started treatment with immunoadsorption or plasmapheresis as soon as possible because previous studies demonstrated that success of treatment was better with an early start (9). Immunoadsorption and plasmapheresis represent the most common therapeutic approach with complete or partial remission of proteinuria achieved in 65% of treated adults as shown by retrospective studies (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Prior to the routine use of plasmapheresis graft failure owing to recurrent FSGS was up to 80% (10).…”
Section: Plasmapheresis In Fsgs Recurrence 441mentioning
confidence: 99%
“…Protective effects of preemptive plasmapheresis have been reported (11,12). Results in the literature show that 65% of adults with recurrent FSGS treated with plasmapheresis or immunoadsorption experienced partial or complete remission of proteinuria (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The rationale for the use of this treatment is removal of causative circulating permeability factor.…”
mentioning
confidence: 99%
“…1,2 It is most frequently seen in the immediate phases after kidney transplantation (KTx), suggesting that podocyte injury is probably caused by a circulating factor, initially thought to be released by T cells. 3 A potential circulating factor, altering the glomerular permeability, has been identified as a 30-50 kd protein. 4,5 The most recent, strongest, evidence for the presumed permeability factor relates to a soluble urokinase receptor, the soluble form of the urokinase type plasminogen (suPAR).…”
Section: Introductionmentioning
confidence: 99%
“…Ren Fail, Early Online:[1][2][3][4][5][6][7] Ren Fail Downloaded from informahealthcare.com by University of Otago on 07/28/15For personal use only.…”
mentioning
confidence: 99%
“…Nel 1999, un importante studio multicentrico che ho già ricordato (5) evidenziava come, in una casistica di 25 bambini con recidiva di FSGS nel trapianto, la presenza di fattori circolanti di permeabilità aveva un valore predittivo di recidiva e che il trattamento con PEX associato alla terapia con ciclofosfamide induceva la remissione nella maggioranza dei casi. Nel 2001, il nostro gruppo di Pisa pubblicava i risultati del trattamento di 7 pazienti con FSGS dei reni nativi e del rene trapiantato (15): negli anni successivi si aggiungevano 3 casi per un totale di 10: 7 con malattia dei reni nativi e 3 con recidiva nel rene trapiantato, 7 trattati con IAA e 3 con PEX; 2 su 3 casi con recidiva e 3 su 7 con FSGS dei reni nativi ottenevano remissione. Il ciclo di terapia aferetica era costante nei pazienti identificare alcune piccole proteine di peso molecolare intorno ai 30 kD (3), capaci di svolgere un'attività permeabilizzante dei capillari glomerulari e, quindi, capaci di indurre proteinuria: VPF (vascular permeability factor): linfochina prodotta da linfociti T; agisce sulla permeabilità capillare sistemica e glomerulare.…”
Section: Revisione Dei Principali Studi Su Plasmaferesi E Immunoadsorunclassified